New records of Anomala tibialis Lansberge, 1886 and a new replacement name for Anomala tibialis Schaeffer, 1906 (Coleoptera: Scarabaeidae: Rutelinae: Anomalini) - Seidel, Matthias (Zootaxa, 2021)
The species Anomala tibialis Schaeffer, 1906 (Coleoptera: Scarabaeidae: Rutelinae: Anomalini) was described based on a single specimen from Texas, United States of America, and is currently treated as a valid species. However, Anomala tibialis Schaeffer, 1906 is a junior homonym of the widespread African Anomala tibialis Lansberge, 1886. This primary junior homonym has no known available and potentially valid synonyms and must therefore be rejected and replaced by a new substitute name (International Commission on Zoological Nomenclature 1999, Articles 57.2 and 60.1). In this paper, full bibliography, distribution data, and new records for the species concerned are provided, and a new replacement name for Anomala tibialis Schaeffer, 1906 is established.